Genomic Diversity of Group A Rotavirus Strains Infecting Humans in Eastern India - Das, Soma (American Society for Microbiology, 2002)
Between 1998 and 2000, a total of 266 samples were found positive for group A rotaviruses by RNA electrophoresis. Samples were collected from patients admitted to two leading hospitals in Calcutta. Serotyping could be done only with 22% of the positive samples, leaving 78% untypeable. The G (VP7 genotypes) and P (VP4 genotypes) types were determined for 159 samples by reverse transcription and multiplex PCR. The predominant genotype was G1P[8] (20%), followed by G2P[4] (15%) and G4P[8] (6%). A number of uncommon genotypes, G1P[4] (4%), G2P[8] (2.5%), G2P[6] (0.6%), G4P[4] (2.5%), and G4P[6] (1.25%), were also detected during this study period. Twenty two percent of specimens showed mixed infections, 38 (24%) of the total samples remained untypeable for either VP7 or VP4, while only 4 (2.5%) of the samples were untypeable for both genes. Eleven specimens collected from Manipur were also genotyped and revealed a very high degree of genomic reassortment.